Treatment adherence and the contemporary approach to treating type 2 diabetes mellitus - Kolars, Bela; Minakovic, Ivana; Grabovac, Beata; Zivanovic, Dejan; Mijatovic Jovin, Vesna (Biomedical papers, 2024)
The rising burden of type 2 diabetes mellitus (T2D) poses a significant healthcare challenge on a global scale. The economic impact is also substantial and continually increasing. In Serbia, even though the prevalence is officially around 12 percent, nearly 40 percent of the adult population is estimated to be living with undiagnosed diabetes and more than half the population is obese or overweight. This review comprehensively addresses the present approach to treating T2D, emphasizing the critical role of treatment adherence. We review the various components of T2D treatment, underlining the significance of lifestyle modifications. The pros and cons of medications used in treatment are discussed and factors influencing adherence are analysed. A healthy lifestyle remains the foundation of the treatment, and if not sufficient, early pharmacotherapy is initiated. Medications have been developed to lower blood sugar levels with cardiorenal protection, however, due to their still high cost, metformin remains the drug of first choice for most patients. Adherence to the treatment regimen is often poor. Factors associated with this are diverse and often multiple in a particular patient. Poor adherence is associated with poor glycaemic control, increased risk of disease complications, higher cardiovascular risk, increased mortality, hospitalizations, and healthcare costs. In addition to reducing the complexity of drug therapy and better informing the patient, improved education and motivation could lead to greater adherence. Enhanced communication between the patient and the physician and reduced treatment costs could also have a positive impact. The review concludes that addressing factors affecting adherence can significantly improve T2D outcomes and reduce costs. Further research is needed to identify region-specific risk factors for poor adherence.
Keywords: type 2 diabetes mellitus; antidiabetic drugs; adherence; compliance